Driving Sustainable Solutions: Exploring Supported-Polyoxometalate Catalysts for Enhanced Oxidative Desulfurization - Sophia June C Ng; Angelo Earvin S Choi; Nathaniel P Dugos; Meng-Wei Wan (Chemical Engineering Transactions)
Sulfur oxides that originate from fuels can cause compounding damage to the environment if left unchecked. As such, deeper desulfurization methods have been researched for higher sulfur conversion for cleaner fuels. Oxidative desulfurization (ODS) is a promising substitute for hydrodesulfurization as it focuses on organosulfur compounds and has lower reaction conditions. Improving the conversion percent involves several parameters, such as reaction temperature, oxidant concentration, catalyst dosage, and catalyst nature. One of the most efficient catalysts for ODS is polyoxometalates. They are homogeneous catalysts with transition metal centers. This makes it difficult to extract from the fuel to reuse in another ODS cycle. This paper reviews the available supports for polyoxometalate catalysts which help increase recyclability and conversion efficiency. Supports create heterogeneous catalysts that are easier to extract after ODS. These include metal oxides, activated carbon, silica, and metal-organic frameworks (MOF). Metal oxides tend to be the most stable due to strong intermolecular bonds between the polyoxometalate and the metal. They can also be customized depending on the catalyst requirements. Activated carbon and silica are incredibly porous which are desirable qualities for a heterogeneous catalyst. It allows for more sulfur to adhere to the surface of the catalyst which increases the conversion percentage. MOFs have the benefit of being porous while also having adsorptive desulfurization capabilities. Increasing recyclability can increase the volume of desulfurized fuel while reducing costs.